ANALISA KUALITAS AIR SUNGAI SILAHI SALBE DAN KELUHAN KESEHATAN KULIT MASYARAKAT DESA TOGU DOMU NAULI KECAMATAN DOLOK PARDAMEAN KABUPATEN SIMALUNGUN TAHUN 2013 - bestti Star Pohan; nurmaini *; irnawati marsaulina (Lingkungan dan Kesehatan Kerja, 2014)
Analysis of Silahi rivers water quality and health disorders at comunity on ToguDomu Nauli village, Sub-district Dolok Pardamean, Simalungun regency. Silahi river waterwas one of water source which used by Togu Domu Nauli people. In order to assure waterquality which used by people is safety therefore need a water quality control. The purpose ofthis study is to analyze Silahi river water quality for physic quality, biological quality,chemical quality and health disorders which sequanced by river water used. The method usedwas decriptive, crossectinal study with 384 population. Sampling based on simple randomsampling thus got 79 sample. The result are obtained that physic quality of Silahi river waterThe physical parameters which are not eligible for health which,colors 36.1-38.2 TCU,turbidity ranged from 0.95 to 1.13 NTU. While qualified temperature at 22.10C, TDS 57-59mg/l, TSS, 7-12 mg/l, is odorless. Chemical parameters which are not eligible for health orquality that is above standards DO revolves around 7.31-7.50 mg/l BOD range 2.7-5.09 mg/ll, COD range 7.0-10.4 mg/l. The parameters meet the standard quality raw pH 7.0-7.2,ammoniac-0.0003 0.0005 mg/l, phosphate 0.08-0.20, nitrate 1.4-1.7 mg/l, DO 7.31-7.50 mg/l,total coliform 38-140/100 ml, colifaecal 9 -70/100 ml.The results of study indicate thatpercentage of respondent with the skin diseases is 57 people (74.0%). So suggested to makewater filter, further research needs to be done about the water quality of Lake Toba aroundthe village of Nauli, Domu and Togu research about personal hygiene Togu Domu Naulivillage community.Keywords: Water, Skin health disorders,quality of the river water